The fishing industry of Minicoy Island with special reference to the tuna fishery - Jones, S; Kumaran, M (Indian Journal of Fisheries, 2016)
The coral island of Minicoy (Fig. 1 a and b) in the Indian Ocean (Latitude 8Â° 7' N., Longitude 73Â° 18' E.) is the most important tuna fishing centre in the Indian Union (Fig. 1). Situated between the two main groups of islands of the Laccadive and the Maldive Archipelagoes, it is about 10 km. long and 820 m. broad in the centre and has an area of about 455 hectares and population of about 4,000 who speak the same Mahl dialect as the Maldivians to whom they are related ethnically. The main port of trade in India for the islanders is Cannanore about 420 km. away on the Malabar coast and specially built sailing vessels known as odams are used for carrying men and cargo to the mainland and back.